2012
DOI: 10.4236/jwarp.2012.45035
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Water Foot Print and Virtual Water Budget in Iran Related to the Consumption of Crop Products by Conserving Irrigation Efficiency

Abstract: In this study we estimate agricultural water footprint and its components from consumption perspective in arid and semi-arid region like Iran. This study is based on blue water consumption in irrigated land. Iran has imported net virtual water about 11.64 billion cubic meters (bcm) as international crop trade in [2005][2006]. Therefore, Iran has depended on virtual water imports. By conserving about 60% irrigation efficiency, the total water requirement to produce imported crops in Iran is nearly 20.78 billion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…As such, this study investigated virtual water transfer patterns in Iran, which have been proven to have a key role in global water savings [58]. Unlike other studies that concluded that Iran was a net virtual water importer [13,52,59], we showed that Iran exported 1811 Mm 3 of water.…”
Section: Major Destinations Of Exports and Water-intensive Trade Strumentioning
confidence: 71%
“…As such, this study investigated virtual water transfer patterns in Iran, which have been proven to have a key role in global water savings [58]. Unlike other studies that concluded that Iran was a net virtual water importer [13,52,59], we showed that Iran exported 1811 Mm 3 of water.…”
Section: Major Destinations Of Exports and Water-intensive Trade Strumentioning
confidence: 71%
“…At provincial level Zhao et al, 27 estimated the regional water footprint of Leshan city in China. At country level, Kampman, 28 Ahmed and Ribbe, 29 Ge et al, 30 , Arabi et al, 31 quantified the WF of India, rainfed and irrigated areas of Sudan, China and Iran. Chapagain and Hoekstra 32 quantified the water footprint of rice at global level from production and consumption perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few studies conducted to investigate the impact of spatial variations of climate, management and soil on the agricultural water footprint in Iran (Montazar and Zadbagher, ; Ababaei and Ramezani Etedali, , ; Bazrafshan et al ., ). Most of water footprint (WF) studies conducted across the country have been limited to small areas or a specific crop (Dehghanpur and Bakhshoodeh, ; Arabi et al ., ; Babazadeh and Sarai Tabrizi, ; Pourjafarinejad et al ., ; Omidi and Homaee, ). These studies do not provide a thorough insight into the main issues and do not help in devising effective policies.…”
Section: Introductionmentioning
confidence: 99%
“…Iran's population will reach about 89 million by 2030 (United Nations (UN), 2015). This population will need 150 Gm 3 yr À1 (giga cubic metres per year) of water to supply food security based on 2.6 million calories of energy per capita (Alizadeh and Keshavarz, 2005;Arabi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%